2016
DOI: 10.1111/crj.12570
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and rhinitis in a Tunisian population

Abstract: Asthma and rhinitis represent a considerable public health problem in children and adults up to age 52 in Tunisian population. Our results confirm also the strong association between them. These findings highlight the need for a clinical global assessment of asthma together with rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
1
2
0
6
Order By: Relevance
“…The present study found the asthma prevalence rate among older adults was consistent with a multi-site study conducted earlier (2007-2010) [40], but lower than corresponding rates reported in independent surveys conducted in other African countries: 2.7% in Cameroon (�19 years) [7], 4.3% in Gambia (�15 years) [8], 5.3% in Botswana (10-64 years) [9], 6.5% in Tunisia (2-52 years) [10], 6.8% in Uganda (�35 years) [11], 6.9% in Kinshasa (�18 years) [12] and 15.2% in Nigeria (18-65 years) [13]. The asthma prevalence rate in the present study is also lower than has been reported in United States, 7.7% (� 18 years) [41] and 7.2% in Israel (�21 years) [42], but it exceeds the asthma prevalence rate of 1.24% reported in China (�14 years) [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study found the asthma prevalence rate among older adults was consistent with a multi-site study conducted earlier (2007-2010) [40], but lower than corresponding rates reported in independent surveys conducted in other African countries: 2.7% in Cameroon (�19 years) [7], 4.3% in Gambia (�15 years) [8], 5.3% in Botswana (10-64 years) [9], 6.5% in Tunisia (2-52 years) [10], 6.8% in Uganda (�35 years) [11], 6.9% in Kinshasa (�18 years) [12] and 15.2% in Nigeria (18-65 years) [13]. The asthma prevalence rate in the present study is also lower than has been reported in United States, 7.7% (� 18 years) [41] and 7.2% in Israel (�21 years) [42], but it exceeds the asthma prevalence rate of 1.24% reported in China (�14 years) [31].…”
Section: Discussionsupporting
confidence: 89%
“…The Global Initiative for Asthma estimates that asthma affects 300 million people globally and 50 million people in Africa [6]. Asthma prevalence varies across Africa, as reported in several independent, cross-sectional studies providing country estimates of 2.7% in Cameroon (�19 years) [7], 4.3% in Gambia (�15 years) [8], 5.3% in Botswana (10-64 years) [9], 6.5% in Tunisia (2-52 years) [10], 6.8% in Uganda (�35 years) [11], 6.9% in Kinshasa (�18 years) [12] and 15.2% in Nigeria (18-65 years) [13]. The range of ages included in specific studies, along with differences in case definition, make comparisons difficult across countries in and outside of Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, patients were given the validated Portuguese version of the International Study of Asthma and Allergies in Childhood (ISAAC) for perennial and seasonal allergic rhinitis questionnaire 25 , and the MIDAS translated into Portuguese 26 . Although the ISAAC questionnaire was originally created for evaluating children and adolescents, several studies worldwide have employed it with adults in the last decade 27 . Participants diagnosed with asthma were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Em outros estudos, a comorbidade rinite alérgica variou entre 37% e 49% (VIZUETE et al,., 2019). Em estudo da Tunísia, a prevalência da rinite alérgica em asmáticos foi de 48,8% (SONIA et al,., 2018), dados similares aos encontrados na pesquisa. Pacientes com asma alérgica de início precoce tendem a apresentar uma associação clara entre a exposição a alérgenos e os sintomas, bem como entre os sintomas das vias aéreas superiores e inferiores (PORSBJERG, MENZIES-GOW, 2017).…”
Section: Comorbidades Dos Pacientesunclassified
“…Pacientes com asma alérgica de início precoce tendem a apresentar uma associação clara entre a exposição a alérgenos e os sintomas, bem como entre os sintomas das vias aéreas superiores e inferiores (PORSBJERG, MENZIES-GOW, 2017). Além disso, é observado que os asmáticos com rinite alérgica associada relatam mais sintomas respiratórios, com pior controle da doença, demostrando exacerbações mais frequentes e mais atendimentos hospitalares (PORSBJERG, MENZIES-GOW, 2017;SONIA et al,., 2018).…”
Section: Comorbidades Dos Pacientesunclassified